2007
DOI: 10.1111/j.1468-2958.2007.00297.x
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Reactance and Promotional Health Messages: The Effects of Controlling Language, Lexical Concreteness, and the Restoration of Freedom

Abstract: Recent social influence research utilizing psychological reactance theory (J. W. Brehm, 1966) has focused on how reactance motivates message rejection due to threats to perceived freedoms posed by controlling language. Although reactance has been shown to increase message rejection and source derogation, persuasive appeals employing alternative forms of restoration of freedom, as suggested by the theory, have received little if any empirical scrutiny. The present study manipulated the levels of controlling lan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

24
402
6
5

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 327 publications
(447 citation statements)
references
References 36 publications
24
402
6
5
Order By: Relevance
“…[6,8,9,17,19,[21][22][23]25]. This research indicates that when language becomes more controlling, people are more prone to respond in 1 The original theory of psychological reactance [3] speaks of perceived freedom instead of perceived autonomy.…”
Section: Psychological Reactancementioning
confidence: 96%
See 4 more Smart Citations
“…[6,8,9,17,19,[21][22][23]25]. This research indicates that when language becomes more controlling, people are more prone to respond in 1 The original theory of psychological reactance [3] speaks of perceived freedom instead of perceived autonomy.…”
Section: Psychological Reactancementioning
confidence: 96%
“…A study by Miller and colleagues [17] provided insights in the underlying processes leading to psychological reactance. This research indicated that the use of concrete (descriptive) language that avoids any doubts about the meaning of the message, resulted in more compliant behavior.…”
Section: Psychological Reactancementioning
confidence: 99%
See 3 more Smart Citations